A Novel in vivo Anti-amnesic Agent, Specially Designed to Express Both Acetylcholinesterase (AChE) Inhibitory, Serotonergic Subtype 4 Receptor (5-HT4R) Agonist and Serotonergic Subtype 6 Receptor (5-HT6R) Inverse Agonist Activities, With a Potential Interest Against Alzheimer’s Disease - Hatat, Bérénice; Yahiaoui, Samir; Lecoutey, Cédric; Davis, Audrey; Freret, Thomas; Boulouard, Michel; Claeysen, Sylvie; Rochais, Christophe; Dallemagne, Patrick (Frontiers in Aging Neuroscience, 2019)
This work describes the conception, synthesis, in vitro and in vivo biological evaluation of novel Multi-Target Directed Ligands (MTDL) able to both activate 5-HT4 receptors, block 5-HT6 receptors and inhibit acetylcholinesterase activity (AChE), in order to exert a synergistic anti-amnesic effect, potentially useful in the treatment of Alzheimer’s disease (AD). Indeed, both activation of 5-HT4 and blockage of 5-HT6 receptors led to an enhanced acetylcholine release, suggesting it could lead to efficiently restoring the cholinergic neurotransmission deficit observed in AD. Furthermore, 5-HT4 receptor agonists are able to promote the non-amyloidogenic cleavage of the amyloid precursor protein (APP) and to favor the production of the neurotrophic protein sAPPα. Finally, we identified a pleiotropic compound, [1-(4-amino-5-chloro-2-methoxyphenyl)-3-(1-(3-methylbenzyl)piperidin-4-yl)propan-1-one fumaric acid salt (10)], which displayed in vivo an anti-amnesic effect in a model of scopolamine-induced deficit of working memory at a dose of 0.3 mg/kg.